UPAYA PENCAPAIAN TARGET PENERIMAAN PENDAPATAN ASLI DAERAH (PAD) YANG BERSUMBER DARI RETRIBUSI DAERAH MELALUI TRANSAKSI NON TUNAI DI KABUPATEN PURWOREJO (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
This study aims to evaluate the implementation of non-cash transactions (NCT) for the payment of regional retribution. identify, and analyze the causes of the use of NCT to achieve the target of regional retribution receipts that have not been maximized, and formulate efforts to increase the achievement of regional retribution revenue targets through NCT in Purworejo Regency. The method used is descriptive qualitative. The results showed that the receipt of retribution for waste/cleaning services managed by the Environmental Service (DLH) decreased due to lack of socialization of the provisions for retribution services for waste/cleaning services, socialization of payments using NCT was not massive, and commitment and concern of DLH for efforts to achieve revenue targets were still lacking. The reason for not achieving the target of receiving regional retribution through NCT in Purworejo Regency is the lack of socialization of retribution for waste/cleaning services and NCT for paying regional retributions; the regency government socialization media has not been fully utilized; NCT supporting infrastructure is limited; budget that supports increased revenue through NCT is limited; coordination and communication between stakeholders has not been intensive; human resources in revenue management service in Purworejo are limited and need to upgrade their IT knowledge. Efforts to increase the achievement of the target of receiving regional retribution through NCT in Purworejo Regency are the socialization of Regional Regulation No. 7 of 2011 concerning Retribution for Waste/Cleaning Services, coordination with collection officers for achieving targets, socialization of NCT regional retribution payments using media owned by the Regency Government massively, coordination meetings and evaluation to identify obstacles that occur in each revenue management service in Purworejo, scrutiny of planning and budgeting expenditures in the context of collecting retribution by each revenue management service in Purworejo.
Keywords: non-cash transactions; regional retribution; efforts to achieve the target of receiving regional retribution